2002
DOI: 10.1163/156854102760290491
|View full text |Cite
|
Sign up to set email alerts
|

Variation in virulence of cereal cyst nematode populations from North Africa and Asia

Abstract: Eight populations of Heterodera avenae, H. lipjevi and H. latipons were tested in Petri dishes with six cereal differentials of the International Test Assortment and a set of resistant genotypes of wheats. Ratios of white females/juveniles inoculated were equivalent to those obtained previously in tubes and pots and con rmed the validity of the miniaturised technique used to study the virulence/resistance relationships of these nematodes and cereals. The populations were differentiated by virulence to barley d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Heterodera avenae is found in temperate wheatproducing regions throughout the world, including North and South Africa (Mokabli et al, 2002), Australia (Kort, 1972), Europe (Sikora, 1988;Rivoal and Cook, 1993), the Middle East (Ibrahim et al, 1999), and North America (Smiley, 1994). The yield reduction of wheat caused by H. avenae is 15%-20% in Pakistan (Maqbool, 1988), 40%-90% in Saudi Arabia (Ibrahim et al, 1999), and 23%-50% in Australia (Nicol et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Heterodera avenae is found in temperate wheatproducing regions throughout the world, including North and South Africa (Mokabli et al, 2002), Australia (Kort, 1972), Europe (Sikora, 1988;Rivoal and Cook, 1993), the Middle East (Ibrahim et al, 1999), and North America (Smiley, 1994). The yield reduction of wheat caused by H. avenae is 15%-20% in Pakistan (Maqbool, 1988), 40%-90% in Saudi Arabia (Ibrahim et al, 1999), and 23%-50% in Australia (Nicol et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of this nematode was first discovered and reported by Scotto La Massese (1961) and by Lamberti et al (1975). However, recent studies have reported that this species was detected in various cereal growing areas of Algeria (Mokabli et al 2001;Valette et al 2002;Tirchi et al 2016). Heterodera filipjevi appears mostly in Mediterranean and European countries (Rumpenhorst et al 2003;Dababat 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Different studies showed that the Cre1 locus is relatively more responsive to H. avenae population from Europe, North America and North Africa (Table 2) whereas this locus is less responsive to Australian and Asian populations of CCNs (Rivoal et al, 2001;Mokabli et al, 2002). In addition to different responsiveness of Cre loci in different countries and continents, the effectiveness of Cre genes varies in response to different species of CCNs (Ali et al, 2019).…”
Section: Source Of Resistance To Cereal Cyst Nematodes (Ccn)mentioning
confidence: 98%